Clinical Evaluation of Radio-Labelled Bleomycin for Tumor Detection - Rasker, J. J.; Beekhuis, H.; van de Poll, M.A.P.C.; Versluis, A.; Jurjens, H.; Woldring, M.G. (Nuklearmedizin - NuclearMedicine, 1978)
Investigations with bleomycin labelled with radionuclides other than 57Co in patients with cancer and in tumor-bearing animals are described. In patients 57Co-bleo appears to be a better tumor-seeking radiopharmaceutical than 111In-bleo, 99mTc-bleo or 197Hg-bleo. This can be explained by a higher stability in vivo and a better tumor-seeking property of 57Co-bleo and less disturbing activity in the cardiac pool and in bone and other normal tissues when assessing the scintigram.Results with 111In-bleo labelled in acidic solution are not essentially different from those with 111In-bleo labelled in neutral solution.Results of 197Hg-bleo are almost identical with those of 197HgCl2 regarding the tumor-seeking effect as well as the distribution in normal tissues and organs. Probably the complex of 197Hg to bleomycin is not stable in vivo. The superiority of 57Co-bleo over 99mTc-bleo, 197Hg-bleo and also over 67Cu-bleo is confirmed by experiments on tumor bearing animals.We may conclude that the indication for use of bleomycin as a tumor-seeking pharmaceutical labelled with 111In, 99mTc, 197Hg or 67Cu seems to be very limited.